PRODUK UNGGULAN DAN IMPLIMENTASINYA DI KABUPATEN ACEH UTARA - Muhammad Nasir; Yetti Tri Putri; Lianti Lianti; Nurmila Dewi; Hilmi Hilmi (Politeknik Negeri Lhokseumawe, 2018)
This study aimed to know the featured commodity and commodity and potential businesses which is yet to be superior, but has the potential to excel in the future if they are given a special treatment or policies; and provide recommendations which commodities or featured businesses that need / could be developed in each sub-district. Besides, it also increases the role of banks in the development featured KPJu and District Government’s policies, which is also associated with the Provincial and Central Government policies, in order to develop the featured commodity as well as small and medium businesses. The data used in this research is secondary data collected from the Central Statistical Bureau and also from other relevant sources. Meanwhile the primary data are achieved from interviews with stakeholders in the sub-district and district level through Focus Group Disscusion (FGD). The results of this study indicate that commodities such as palm oil, rice, cocoa, fishing at sea, chili, rubber, durian and livestock is very good to be developed in North Aceh District. However necessary assistance for the featured KPJu SMEs is very crucial and needs to be intensified and implemented sustainably. In connection with that, the involvement of institutional companion such as Business Development Service (BDS) or the existing SMEs Business Incubator need to be further enhanced in term of their role and function with the support of Universities and related Institutions. Moreover, there is also a need for a continuation of the current collaboration between the Regional Government and local College in the area, of which needs to be improved and developed. The three universities obligation knows as Tridharma Universitas in Indonesia, in particular dharma Community Services, as well as co-curricular programs such as on the job training or other co-curricular activities should be developed as an assistance program of the featured SMEs KPJu.Keywords: AHP modification, local featured commodity and poverty alleviating strategy